Arteriovenous Fistula Pseudoaneurysm Mimicking Cutaneous a Neoplasm Arising from a Stenosed Arteriovenous Fistula - Hayato Hanada; Shiro Niiyama; Akiko Hirata (Journal of Plastic and Reconstructive Surgery)
A 72-year-old woman was referred for noticing a nodule on the arteriovenous fistula spontaneous obstruction. Physical examination revealed a dark reddish, non-pulsatile nodule in the right forearm that measured 21 × 13 mm, bled easily, and was partially crusted. During the course of examinations, the patient developed trauma-induced excessive bleeding from the lesion. At the initial examination, based on the clinical findings, we considered the possibility of cutaneous neoplasm. Eventually, we made the diagnosis of an organized hematoma and an arteriovenous fistula pseudoaneurysm. No previous report of an arteriovenous fistula pseudoaneurysm mimicking a neoplasm arising from a stenosed arteriovenous fistula, as in our case, has been available. An arteriovenous fistula pseudoaneurysm can arise even from a stenosed arteriovenous fistula, so that an early diagnosis can be made and impending rupture prevented.